CONTEMPORARY CHEST RADIOGRAPHIC MANIFESTATIONS OF PULMONARY TUBERCULOSIS INFECTION WITH HIV/AIDS COINFECTION : A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS AND PRIMARY STUDIES - Rahma Adinda; Nindi Elis; Hikmatul Lailiyah (International Medical Journal Corp. Ltd, 2026)
Introduction: Tuberculosis (TB) remains the leading infectious cause of death among people living with HIV (PLHIV), with chest radiography (CXR) as the primary imaging modality in high-burden settings. Progressive CD4+ T-lymphocyte depletion disrupts granulomatous containment, producing